CHARACTERIZATION OF WHEAT VARIETIES ( ARIETIES (TRITICUM TRITICUM TRITICUM SPP.) THROUGH CHEMICAL TESTS THROUGH CHEMICAL TESTS - UKANI, J. D; RAMANI, P. S; BABARIYA, C. A (The Bioscan, 2016)
An experiment was carried out at the Department of Seed Science and Technology, Junagadh Agricultural University, Junagadh, to characterize 28 wheat varieties of different species (17 of Triticum aestivum, 9 of Triticum durum and 2 of Triticum dicoccum) released for general cultivation in Gujarat at state level as well as at the National level in Central India based on the chemical tests. The seeds were subjected to phenol, peroxidase, NaOH and KOH test for differentiating the varieties. Based on the seed colouration with phenol, varieties were grouped into absent (6), light brown (9), brown (5) and dark brown (8) in colour. Based on the colour of the solution due to peroxidase activity, varieties were grouped into four categories viz., absent (4), light brown (11), brown (8) and dark brown (5) coloured types. Based on the colour of the seed coat due to NaOH solution, the varieties were grouped into straw coloured (26) and orange (2) in colour reaction. However, the KOH test did not differentiate any wheat varieties studied. All the varieties were negative (no colour to the solution) in response. Therefore, it can be concluded that varieties can be identified on the basic of chemical tests like phenol, peroxidase and NaOH tests